Trend analysis of water quality indicator parameters in a tropical reservoir - Márquez-Pacheco, Henri; Leyva-Morales, José Belisario; Davizón-Castillo, Yasser Alberto; Ontiveros-García, Luz Adriana; Amillano-Cisneros, Jesús Mateo (Ecosistemas y Recursos Agropecuarios, 2023)
The growth of the population and agricultural production, along with the increase in industrialization worldwide have deteriorated the quality of water in continental water bodies. The objective of this work was to analyze the trend of water quality parameters in a tropical reservoir from Center-South region of the State of Sinaloa, Mexico, applying Mann-Kendall non-parametric statistical analysis. Data obtained at four sampling points in the El Salto dam during the period 2012-2020 were used. The results obtained indicate that the water quality in the reservoir presents a significant tendency to improve during the period analyzed. The reservoir showed contamination of organic matter. In addition, that the concentration of fecal-coliforms exceeds the ecological criteria for water quality as a source of drinking water supply and agricultural irrigation. Likewise, the concentrations of nutrients, chlorophyll-a and visibility of the Secchi disc classify the dam water between eutrophic and hyper eutrophic.